2005
DOI: 10.1532/hsf98.20041146
|View full text |Cite
|
Sign up to set email alerts
|

Brain Magnetic Resonance Imaging Abnormalities following Off-Pump Cardiac Surgery

Abstract: Ischemic lesions found at DW-MRI are seen after off-pump CABG at a rate similar to that reported for CABG with cardiopulmonary bypass. This finding suggests that these lesions are not totally due to cardiopulmonary bypass. Further prospective clinical studies would be helpful for determining which factors are causally related to brain ischemia following CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…27 Contrary to our findings, Friday et al 28 reported that new DW-MRI lesions were present in five (31%) of 16 patients after OPCAB surgery. Unfortunately, the authors did not report on the extent and severity of aortic atheroma.…”
Section: Discussioncontrasting
confidence: 99%
“…27 Contrary to our findings, Friday et al 28 reported that new DW-MRI lesions were present in five (31%) of 16 patients after OPCAB surgery. Unfortunately, the authors did not report on the extent and severity of aortic atheroma.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding suggests that factors other than the use of the cardiopulmonary bypass are associated with postoperative ischemic lesions. 71 With a stroke rate of only 2% to 5% in the CABG group, it takes a study involving a large number of patients to reliably establish the beneficial effects of an alternative procedure, and most studies in the literature have sample sizes too small to show statistical significance. Nevertheless, a large study by Bucerius (nϭ16 184) found a difference in the incidence of stroke between conventional CABG (3.9%) and off pump group (2.5%), 10 indicating that stroke risk was reduced but not eliminated with this alternative procedure.…”
Section: Stroke After Other Cardiac Interventionsmentioning
confidence: 99%
“…[20] In a recent study, new diffusionweighted MRI lesions were found in five of 16 patients (31%) undergoing off-pump CABG. [21] In our study, new lesions were assessed using the same imaging modality and we found no statistically significant difference between the two groups in terms of the frequency and number of these lesions.…”
Section: Discussionmentioning
confidence: 53%